Pesticide Injection and Drenching - Frederick M. Fishel (EDIS, 2018)
Drenching and injection are two pesticide application methods that are particularly effective in controlling some of the most troublesome insect pests of ornamental landscape trees. This 4-page document describes the equipment and procedures you will need to carry out either of these methods. Written by Frederick M. Fishel and published by the UF/IFAS Agronomy Department, January 2018. http://edis.ifas.ufl.edu/pi274